Respiratory lesions in IgG4-related disease: classification using 2019 American College of Rheumatology/European League Against Rheumatism criteria. Issue 3 (12th September 2022) - Komatsu, Masamichi; Yamamoto, Hiroshi; Matsui, Shoko; Terasaki, Yasuhiro; Hebisawa, Akira; Iwasawa, Tae; Johkoh, Takeshi; Baba, Tomohisa; Miyamoto, Atsushi; Handa, Tomohiro; Tomii, Keisuke; Waseda, Yuko; et al.
In 2019, the American College of Rheumatology (ACR) and the European League Against Rheumatism (EULAR) proposed classification criteria for IgG4-related disease (IgG4-RD) [1, 2]. IgG4-RD can cause fibroinflammatory lesions characterised by infiltration of abundant IgG4-positive plasma cells with fibrosis and an elevated serum IgG4 concentration [3–5]. Approximately 35% of patients with IgG4-RD present with intrathoracic lesions, including those involving the mediastinal lymph nodes, bronchial walls and peribronchovascular bundles [6–8]. To increase diagnostic sensitivity and specificity, we previously proposed diagnostic criteria for IgG4-related respiratory disease (IgG4-RRD) [9]. In this study, ILDs involving IgG4-positive plasma cell infiltration were classified using the 2019 ACR/EULAR criteria. Most IgG4-positive interstitial pneumonia cases were excluded, suggesting the need for a unique treatment strategy. https://bit.ly/38GiUJM